Four heat shock protein genes of the endoparasitoid wasp, Cotesia vestalis, and their transcriptional profiles in relation to developmental stages and temperature. - Min Shi; Ya-Na Wang; Ni Zhu; Xue-Xin Chen (PLoS ONE, 2013)
Heat shock proteins (Hsps) play important roles in the environmental adaptation of various organisms. To explore the functions of Hsps in relation to heat stress and development in Cotesia vestalis, a solitary larval endoparasitoid of Plutella xylostella, four heat shock protein genes, CvHsp40, CvHsc70, CvHsp70 and CvHsp90, were cloned and sequenced from C. vestalis by real-time quantitative PCR and RACE. The cDNA sequence of CvHsp40, CvHsc70, CvHsp70 and CvHsp90 were 1473 bp, 2316 bp, 2279 bp and 2663 bp long, which encode proteins with calculated molecular weights (MW) of 39.1 kDa, 71.2 kDa, 70.1 kDa and 83.3 kDa, respectively. Furthermore, the analysis of genomic DNA confirmed that no introns existed in CvHsp40, CvHsp70 and CvHsp90 while two introns were present in CvHsc70. The amino acid sequence analysis of CvHsps indicated that CvHsp40 is a Type II Hsp40 homolog, CvHsp70 and CvHsc70 are the eukaryotic cytoplasmic Hsp70s, and CvHsp90 is the β-isoform of Hsp90. The divergent transcriptional patterns of CvHsp40, CvHsp70 and CvHsp90 in the different developmental stages suggested that CvHsp transcripts were under different mechanisms of regulation during the development of parasitoid larvae. The dramatic increase of transcripts of CvHsp70 at the third-instar larva coincided with its developmental change in this stage, that is, from inside host to outside host. CvHsp40, CvHsc70 and CvHsp70 showed a trend of sex-specific differences of transcript abundance in the adult stage. All CvHsp transcripts in different developmental stages were significantly induced by heat stress, and the lowest transcript abundances appeared around the temperature 27°C, which probably suggest that this is the most favorable temperature for the development of C. vestalis. Our results suggest that the expression of heat shock proteins reflects to some extent the developmental changes and environmental requirements of insects.